Selectivity and permeation of alkali metal ions in K +-channels - Furini, S; Domene, C (2011)
Ion conduction in K +-channels is usually described in terms of concerted movements of K + progressing in a single file through a narrow pore. Permeation is driven by an incoming ion knocking on those ions already inside the protein. A fine-tuned balance between high-affinity binding and electrostatic repulsive forces between permeant ions is needed to achieve efficient conduction. While K +-channels are known to be highly selective for K + over Na +, some K + channels conduct Na + in the absence of K +. Other ions are known to permeate K +-channels with a more moderate preference and unusual conduction features. We describe an extensive computational study on ion conduction in K +-channels rendering free energy profiles for the translocation of three different alkali ions and some of their mixtures. The free energy maps for Rb + translocation show at atomic level why experimental Rb + conductance is slightly lower than that of K +. In contrast to K + or Rb +, external Na + block K + currents, and the sites where Na + transport is hindered are characterized. Translocation of K +/Na + mixtures is energetically unfavorable owing to the absence of equally spaced ion-binding sites for Na +, excluding Na + from a channel already loaded with K +. © 2011 Elsevier Ltd. All rights reserved.